Therapy response and prognosis of patients with early breast cancer with low positivity for hormone receptors – An analysis of 2765 patients from neoadjuvant clinical trials. (May 2021) - Villegas, Sonia L.; Nekljudova, Valentina; Pfarr, Nicole; Engel, Jutta; Untch, Michael; Schrodi, Simone; Holms, Frank; Ulmer, Hans U.; Fasching, Peter A.; Weber, Karsten E.; Albig, Christian; Heinrichs, Clemens; et al.
Abstract: Aim: To evaluate HER2-negative breast cancer (BC) with a low hormone receptor (HR) expression, with regard to pathological complete response (pCR) and survival, in comparison to triple-negative BC (TNBC) and strong HR-positive BC. Methods: We compared negative [oestrogen (ER) and progesterone receptor (PR) <1%], low-positive (ER and/or PR 1–9%) and strong-positive (ER or PR 10–100%) HR-expression in neoadjuvant clinical trial cohorts (n = 2765) of BC patients. End-points were disease-free survival (DFS), distant-disease free survival (DDFS) and overall survival (OS). We performed RNA sequencing on available tumour tissue samples from patients with low-HR expression (n = 38). Results: Ninety-four (3.4%) patients had low HR-positive tumours, 1769 (64.0%) had strong HR-positive tumours, and 902 (32.6%) had TNBC. There were no significant differences in pCR rates between women with low HR-positive tumours (27.7%) and women with TNBC (35.5%). DFS and DDFS were also not different [for DFS, hazard ratio 1.26, 95%-CI (confidence interval) : 0.87–1.83, log-rank test p = 0.951; for DDFS, hazard ratio 1.17, 95%-CI: 0.78–1.76, log-rank test p = 0.774]. Patients with strong HR-positive tumours had a significantly lower pCR rate (pCR 9.4%; odds ratio 0.38, 95%-CI: 0.23–0.63), but better DFS (hazard ratio 0.48, 95%-CI: 0.33–0.70) and DDFS (hazard ratio 0.49, 95%-CI: 0.33–0.74) than patients with low HR-positive tumours. Molecular subtyping (RNA sequencing) of low HR-positive tumours classified these predominantly into a basal subtype (86.8%). Conclusion: Low HR-positive, HER2-negative tumours have a similar clinical behaviour to TNBC showing high pCR rates and poor survival and also a basal-like gene expression signature. Patients with low HR-positive tumours should be regarded as candidates for therapy strategies targeting TNBC. Highlights: Low positive hormone receptor breast cancer responses to neoadjuvant chemotherapy were analysed. Low positive hormone receptor breast cancer has worse survival than strong positive. Low positive hormone receptor breast cancer mostly expresses basal-like features.